Anti-Malaria Study of Nigella sativa L. Seed Water Extract in Mus musculus Mice Balb C Strain In Vivo - Sosiawan, Tunru Insan; Linda, Weni; Etty, Widyantia (UI Scholars Hub, 2012)
Nigella sativa L. has been reported to exhibit many pharmacological effects, including anti-parasitic properties. This study investigated the anti-malarial effects of a water extract of N. sativa seed in Mus muculus mice infected with the Plasmodium berghei NK65 parasite. The method used was to take a blood parasitaemia count, following the use of Giemsa dye, determining the level of nitric oxide in mice that were infected with P. berghei malaria, using the spectrophotometric method, and determining their survival rate after 20 days of being infected with P. berghei malaria. The results showed that the decrease in the number of parasitaemia and the level of nitric oxide in subjects treated with doses of N. sativa was significant (p < 0.05). Further results showed that P. berghei-infected mice that were given 100 µg/kg of body weight had a better chance of survival. The conclusion is that the provision of N. sativa may reduce the number of malaria parasites and reduce levels of NO. The decrease in the number of parasites may be caused by an immune mechanism, through the regulation of NO levels (lower levels of NO), due to the influence of the anti-oxidant effects of N. sativa. Survival rates of the mice did not show significant results with reduced levels of parasitaemia and NO. This is likely to be because the levels of NO in this group were below the threshold levels at which NO can function as an anti-parasitic. It is alleged that, while NO can function as an anti-parasitic at certain levels, at lower levels its function as an antiparasitic is not optimal. On the other hand, if the levels are too high, damage will result, because of the nature of free-radicals.